Alien Chromosome Serves as a Novel Platform for Multiple Gene Expression in Kluyveromyces marxianus - Yilin Lyu; Jungang Zhou; Yao Yu; Hong Lu (Microorganisms)
Kluyveromyces marxianus is an emerging yeast cell host for diverse products, but multiple-gene expression in K. marxianus faces challenges due to limited current knowledge of cis-regulatory elements and insertion loci. Our previous study transferred an alien Saccharomyces cerevisiae chromosome I (R1) into K. marxianus, resulting in the creation of the monochromosomal hybrid yeast KS-R1. All R1 genes were actively transcribed, providing a series of loci with varying transcriptional activities. Here, we explore the use of R1 as a novel platform for stable, multi-gene integration and expression. By deleting three essential K. marxianus genes while complementing their functions with orthologs on R1, we achieved stable propagation of R1 in the absence of selective pressure. We characterized several loci on R1 that exhibit stable transcriptional activities under various conditions. GFP inserted in place of genes at six such loci demonstrated varying expression levels. Strains with GFP at two loci exhibited significantly higher expression than those with GFP at a single locus. Furthermore, we replaced five R1 genes with disulfide bond formation genes from Pichia pastoris at distinct loci, resulting in the active expression of all five genes and significantly enhanced production of heterologous glucoamylases BadGLA and TeGlaA. Our findings demonstrate that alien chromosomes offer a stable and versatile platform for the coordinated expression of multiple heterologous genes, serving as valuable tools for metabolic engineering and synthetic biology.